Robotic Sensorized Gastroendoscopy with Wireless Single-Hand Control - García, Gabriela; Fischer, Nikola; Marzi, Christian; Mathis-Ullrich, Franziska (Current Directions in Biomedical Engineering, 2022)
The manipulation of flexible endoscopes is a procedure that requires great dexterity since it requires the synchronization and use of both hands in parallel. Imprecise handling during gastroendoscopy could harm the digestive tract. Our solution allows the physician to use only one hand to wirelessly control the forward, backward, and tip bending motion. The proposed system provides endoscopic vision and tactile impact force sensing at the tip to detect the force applied to tissue and thus avoid damage. We experimentally evaluate the handling of the robotic system in open space and inside a medical phantom. The results revealed a training effect with less time demand for task completion and reduction of average impact force after only 5 runs. The proposed system was successfully controlled using one hand and, together with the force information, could enhance the physician's experience during endoscopy. Future work will address axial control and an intensive user study with clinical experts.
CRIS-Team Scopus Importer:2023-03-21
Keywords: hand-held control; robotic gastroendoscopy; sensorized; teleoperated